(untitled) (World Bulletin of Education and Learning, 2026)
Over the past few decades, the integration of corpus linguistics into translation studies has led to a fundamental transformation of the field. This paper examines how corpora contribute to contemporary translation research and practice, with particular attention to their role in enhancing translation accuracy, supporting literary analysis, and shaping the development of corpus-based methodologies. By drawing on recent studies, the discussion demonstrates that corpus-driven approaches provide reliable, data-based insights that improve both theoretical understanding and practical outcomes. At the same time, the paper critically evaluates the challenges associated with corpus use, including limitations in data representation and interpretation. Overall, the study argues that corpora have become indispensable tools in modern translation studies, offering both opportunities and complexities that require careful and informed use.